Farmers' Perceptions of the Contribution of Tourism Attractions to Community Welfare in Kambo, Mungkajang District, Palopo City - Muhammad Syihab Zainuddin; Sulfiana Sulfiana; Helda Ibrahim (Journal of Agriculture, 2026)
Tourism attractions greatly contribute to farmers' welfare. Agricultural fields such as orchards can also be tourist attractions that draw visitors, especially if the farms are located in places with beautiful views at high altitudes. This study aims to describe farmers' perceptions of tourist attractions and their contribution to farmers' welfare in Kambo Village, Mungkajang District, Palopo City. This study is a descriptive quantitative study using frequency tabulation and a survey approach. The population of this study was all farmers in Kambo Village, Mungkajang District, Palopo City, numbering around 100 people farmers. The sample size was 100 people, using total sampling technique. The results of this study show: (1) farmers' perceptions of the existence of Kambo tourist attractions were very good, with almost all (100%) responding that they were very good and good criteria in Likert scale. (2) Farmers' perceptions of the contribution of tourist attractions to improving welfare were also very good, with all (100%) respondents answering that the contribution was very good. (3) Farmers' perceptions of the contribution of tourist attractions to farmers' lives were also very good, with all (100%) respondents answering that the contribution of tourist attractions to farmers' welfare was very good. The conclusion of this study is that tourism attractions are very important to be developed in the community so that they can become additional employment opportunities for them.